VULNERABILITY. SOME REMARKS ON THE ROLE OF VULNERABILITY IN THE AI ACT (TEST BioLaw Journal - Rivista di BioDiritto, 2024)
The paper aims to analyze the role of the concept of vulnerability in European Artificial Intelligence regulation (AI Act). The article will be developed in two parts. In the first we will conduct a conceptual analysis of vulnerability in its multiple dimensions, distinguishing between a universal and a particular sense, and between a categorizing and a situational approach. To do so, we will discuss the main lines of philosophical, legal and bioethical debate on the topic. In the second we will investigate the role of vulnerability in the AI Act, commenting on the most significant recurrences and major variations. We will adopt a synoptic look at the evolution of the document, from its first version to the final one, passing through the amendments proposed by the European Parliament. We will argue that in this document vulnerability is understood primarily in a particular sense, while the universal sense remains almost absent or not directly expressed. This absence, as we will show, seems only partially compensated for by the risk-based approach.
Keywords: AI Act; Vulnerability; Risk-Based Approach; EU